Evaluación de tres niveles de Oligosacáridos Mánanos (Saccharomyces cerevisiae) adicionados en dietas balanceadas de Lechones post destete, en la granja porcícola “San Francisco”, Arenillas, El Oro. - Valdivieso Espinoza, Isai Gustavo (2019)
SUMMARY The objective of this work was to evaluate the effect of three levels of Mannan-Oligosaccharides (Saccharomyces cerevisiae) in the post-weaning piglets phase. A completely random design "D.C.A" was used with 3 treatments and 4 repetitions plus an absolute witness, 2 pigs for each experimental unit with a total of 32 pigs. The verification of the measurement of the treatments was carried out with the Tukey test (P˂0.05), the statistical program InfoStat version 2018e was used. Three levels of Mano Oligosaccharides were evaluated (T1=1,5Kgt-1 T2=1,5Kgt-1, T3=3Kgt-1). The variables studied were: Body weight, average food consumption, feed conversion, average weight increase and cost benefit ratio. The productive parameters analyzed with the Tukey P test <0.05, showed significant differences between treatments. The levels of T2 (1,5 Kgt-1) of Mannan-Oligosaccharides added in balanced diets of piglets after weaning, showed higher weights (31.45 kg) in relation to the treatments T0 (witness) and T3 (3 kg), (30,76; 27,24 kg) in the sixth week of the experiment. Higher feed intake was obtained without the addition of Mannan-Oligosaccharides (12,69 kg) in the diet during the sixth week. Greater weight gain obtained the T0 (Witness) in the weeks: one 2,78 kg; two 2,78kg, four 3,93kg, and five 4,65kg. In addition, gain was obtained with the diet of T2 (1,5 kg) of Mannan-Oligosaccharides in week three 4.24 kg, and T1 in the sixth 5,15 kg. Better feed conversion is achieved with the addition of T2 (1,5 kgt-1), (2,39 kg / kg) of Mannan-Oligosaccharides in the diet, in the sixth week of the experiment and Best cost benefits ratio reached T2 (1,5 kgt-1), ($ 1.32) in the diet. Keywords: Oligosaccharides Mánanos, weights, treatment, pigs, food.